(untitled) (Web of Teachers: Inderscience Research, 2025)
The gas distribution mechanism (GTM) is an important part of an automobile engine that provides gas exchange in the cylinder during the operation of the engine. GTM is responsible for introducing an air-fuel mixture into the cylinder and releasing combustion products. This article details the structure, principle of operation, types and importance of GTM. It also provides information on the role of GTM in modern cars and its development trends.